2018
DOI: 10.12681/jhvms.16383
|View full text |Cite
|
Sign up to set email alerts
|

Botanicals: a natural approach to control ascaridiosis in poultry

Abstract: Parasites (protozoa, helminthes, arthropods) represent a main threat for poultry worldwide. Among helminthes, nematodes constitute the most important group of parasites of poultry. The nematode Ascaridia galli, the cause of ascaridiosis in poultry, is one of the most important and prevalent parasites, resulting in serious economic losses, associated with the treatment cost, the decreased feed efficiency, and the poor egg and meat production. During the past few decades the indiscriminate use of anthelmintic dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 36 publications
0
6
0
Order By: Relevance
“…Steroidal alkaloids and aminoglycosides alter nitrate generation and the sugar that reaches the stomach, resulting in unfavorable conditions for parasite development [ 20 ]. Moreover, the piperidine alkaloids pelletierine and arecoline may cause parasite paralysis due to the inhibition of acetylcholine receptors [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Steroidal alkaloids and aminoglycosides alter nitrate generation and the sugar that reaches the stomach, resulting in unfavorable conditions for parasite development [ 20 ]. Moreover, the piperidine alkaloids pelletierine and arecoline may cause parasite paralysis due to the inhibition of acetylcholine receptors [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Stephen et al ( 2022 ) examined Sterospermum kunthianum (Cham-Holl) leaf extracts and their influence on in vitro A. galli egg development and found a concentration-dependency of the plant extract. Like ripleaf (Fayera et al 2018 ), Cham-Holl and A. secundiflora have tanniferous components which are known for their anthelmintic properties such as limiting the availability of nutrients for larvae, inhibiting oxidative phosphorylation in adults and larvae, binding to intestinal larval mucosae and causing thereby autolysis (Symeonidou et al 2018 ). Sen et al ( 2020 ) investigated different extracts of Carica papaya (papaya) in vitro and artificially A. galli infected animals in vivo and showed its high efficiency on larval development in vitro and its FEC reducing abilities in vivo .…”
Section: Discussionmentioning
confidence: 99%
“…Tanniferous plants, such as ripleaf are known for their anthelmintic properties on the larvae and worms themselves (Symeonidou et al 2018 ). Maurer et al (unpublished results) revealed a high in vitro effectiveness of pumpkin seeds, ripleaf and lemongrass oil as a natural anthelmintic depending on the dosage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the preventive measures used by poultry breeders to combat parasitic infection is the use of commercially available anthelmintic agents. With continued use, however, the parasites have established resistance to commercially available anthelmintics (10). In addition, the unavailability of treatment regimen and the cost of anthelmintic drugs impedes village raisers from controlling the impact of parasitism in their flocks.…”
Section: Introductionmentioning
confidence: 99%